Robust Variable Exponent Fixed-Time Speed Control of PMSMs Based on a Fixed-Time Sliding Mode Observer - Varin Cholahan; Napasool Wongvanich; Worapong Tangsrirat (My University, 2025)
This paper presents a state-dependent variable exponent coefficient sliding mode control (VECFSMC). By inducing fixed-time stability analysis, the proposed state-dependent sliding surface provides not only system stability but also a quick response in a fixed period of time. To enhance the controller's ability to direct state trajectories along the sliding surface manifold towards equilibrium and attain the desired outputs despite the presence of disturbances, a fixed-time sliding-mode observer (FTSMO) has been created. The approach is assessed by Lyapunov stability analysis . Eventually, a numerical simulation of composited fixed-time Controller and fixed time Observer evidently shows fast convergence, high robustness against lump disturbances. The proposed technique, along with the fixed-time observer, achieves global fixed-time stabilization and offers straightforward implementation compared to other fixed-time methods, requiring the tuning of fewer parameters.
Keywords: Adaptive Control of Nonlinear Systems; Iterative Learning Control Systems; Control Systems in Engineering